The «ideal city» concept in the modern architecture - Kryvejko, Iryna; Turchyn, Bohdan (Lviv Polytechnic Publishing House, 2016)
The term «ideal city» was clarified in the context of historical development of human civilization. The purpose of our research is to determine features of «ideal city» in the modern architecture, including the process of urbanization. It is concluded that the real challenge for urban infrastructure in the XXI century will become problems related with deficit of energy, solidity of buildings, social-economical and spatial safety of towns people. Two theories about «ideal city» in the XXI century were motivated in this article. First of all, we will focus on the development of big cities (megapolises) for human being (work, rest, regeneration), seconly – we will study the phenomenon of de-urbanization – idea about rejection of urban lifestyle, and return to natural environment, situated out of town.
Keywords: modern architecture; «ideal city»; urbanization; de-urbanization